Policy Persistence and Drift in Organizations - Gieczewski, Germán (Econometrica, 2021)
This paper models the evolution of organizations that allow free entry and exit of members, such as cities and trade unions. In each period, current members choose a policy for the organization. Policy changes attract newcomers and drive away dissatisfied members, altering the set of future policymakers. The resulting feedback effects take the organization down a “slippery slope” that converges to a myopically stable policy, even if the agents are forward‐looking, but convergence becomes slower the more patient they are. The model yields a tractable characterization of the steady state and the transition dynamics. The analysis is also extended to situations in which the organization can exclude members, such as enfranchisement and immigration.